From the Dreadnought to Scapa Flow : the Royal Navy in the Fisher era, 1904-1919. Vol. 3, Jutland and after (May 1916-December 1916). - Marder, Arthur J. (Arthur Jacob), 1910-1981. (London : Oxford University Press, 1966)
This 3rd volume in the 5-part series focuses on May 1916 - December 1916.
Keywords: Great Britain. -- Royal Navy; 1914-1918; World War, 1914-1918 -- Naval operations, British